Pengaruh Work Exhaustion Terhadap Keinginan Berpindah: Studi pada Tenaga Kerja IT di Indonesia - Susanti R. Saragih (Universitas Kristen Maranatha, 2009)
This research aimed to examine the correlation between work factors (work overload, role conflict, role ambiguity, job autonomy and fairness of reward) and work exhaustion in IT professionals. This research is done with premise that the higher work exhaustion, the higher the intention to leave. The questionnaires distribute on website for two months and IT professionals in Indonesia as the respondent. Regression analysis is used to examine the hypothesis. The results showed that role ambiguity and role conflict significantly related to work exhaustion. Work exhaustion also found significantly related to intention to leave. Furthermore, role conflict is found as the dominant antecedent of work exhaustion. Finally, this research suggest some important managerial to HR manager such as the urgency to design a clear job description and manage the workload in IT professionals.